Challenges and opportunities for promoting use of native species for the rehabilitation of degraded silvopastoral systems in Tunisia - Louhaichi, Mounir; Hassan, Sawsan; Jamel, Kailene; Ouled Belgacem, Azaiez (International Center for Agricultural Research in the Dry Areas, 2023)
On September 18, 2023, the One CGIAR initiative on Livestock and Climate, in collaboration with the Direction General des Forets (DGF) and the International Center for Agricultural Research in the Dry Areas (ICARDA), hosted a webinar addressing the challenges and opportunities in leveraging native species for the restoration of degraded silvopastoral systems in Tunisia. The webinar convened 34 participants from diverse national research and development institutions, fostering a rich exchange of perspectives. Key recommendations emerged, including the development of bioclimatic maps for native species, exploration of treated wastewater for sustainable seed propagation, implementation of effective seed treatment and storage, prioritization of multipurpose species for added farmer income, establishment of a pastoratum as a field gene bank, formulation of a comprehensive work program for seed conservation, and the fostering of collaborative partnerships. Additionally, participants urged ICARDA to lead a capacity development initiative on seed collection and conservation, underscoring the webinar's commitment to advancing sustainable pastoral development.